INTEGRATED CONTROL PROJECT BASED ON COST AND TIME: (Implementation Case Study on Job Creation Construction of Videotron LED 6m x 12m in size Baliwerti Project Surabaya) - Al- Qordhowi, Andrian Firdaus Yusuf; Jani, Muaffaq A.; Moetriono, Hary (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
The development and growth of the adult advertising industry in Indonesia is progressing rapidly, characterized by a wide range of advertising models and types. Surabaya, the second largest metropolis after Jakarta, is also actively engaged in the competition for advertisers. In this study, an analysis of the concept of value was conducted using Microsoft Project 2007. By inputting data relevant to the analysis into the program, Microsoft Project automatically performs the necessary calculations according to the predefined formulas. This automation ensures that the results of the value analysis are obtained more quickly and accurately. Based on the above study, it can be concluded that the total forecasted cost of completing the project is Rp. 743,346,765.76, with the project's total incurred cost up to the 9th week being Rp. 679,044,258.74. Consequently, there is a cost savings of Rp. 64,302,507.02, equivalent to an efficiency of 9%. The projected completion time for the project is June 20, 2014 (60 days), but with potential completion in just 51 days, allowing for a nine-day advancement from the planned schedule.